THE OPTIMIZATION OF DRYING IN THE PROCESS OF TAKING GLUCOMMANAN AS PORANG FLOUR (Amorphophallus Spp.) - Sugiarto, Bambang; Proklamagita, Angela Merici Herdyana; Hasibuan, Juana Hizkia; Sulistyowati, RR Endang (Universitas Pembangunan Nasional Veteran Yogayakarta, 2023)
Porang (Amorphophallus Spp.) is one of the Indonesian commodities that are full of benefits because they contain glucomannan, but Porang also contains calcium oxalate, which is dangerous if consumed in large quantities so it requires pre-treatment such as immersion. Besides that, immersion also serves to maintain and improve the physical and chemical quality of Porang. In this research, the immersion media used were water, salt solution (NaCl), vinegar solution (CH3COOH) and ethanol. Porang that have gone through the immersion process are then removed from the water content using spinner and then dried using dehydrator. This research used drying temperature variations of 40°C, 45°C, 50°C, 55°C, and 60°C. The purpose of this research was to obtain the optimal drying temperature for the glucomannan content of Porang flour. Glucomannan content was determined using DNS method. The result showed that each immersion media had a different optimal temperature due to the difference in oxalate released.